For this case we must solve the following equation:
![9 ^ {x + 1} = 27](https://img.qammunity.org/2020/formulas/mathematics/college/90nnne2eg2gvqd4b9z2ftsyvsnqncsvhki.png)
We rewrite:
![9 = 3 * 3 = 3 ^ 2\\27 = 3 * 3 * 3 = 3 ^ 3](https://img.qammunity.org/2020/formulas/mathematics/college/huf0jtsb90dxz78a5n3pe4s37ulac8nko3.png)
Then the expression is:
![3^ {2 (x + 1)} = 3 ^ 3](https://img.qammunity.org/2020/formulas/mathematics/college/q6fgphs3prstvx42t01sugid8ajza8tav7.png)
Since the bases are the same, the two expressions are only equal if the exponents are also equal. So, we have:
![2 (x + 1) = 3](https://img.qammunity.org/2020/formulas/mathematics/college/p8xsp6ckhkoyeos5hbzzvx2rth37p8k40d.png)
We apply distributive property to the terms within parentheses:
![2x + 2 = 3](https://img.qammunity.org/2020/formulas/mathematics/college/ct9kt6bvt6lcajdhj54evtwbby8655wq8g.png)
Subtracting 2 on both sides of the equation:
![2x = 3-2\\2x = 1](https://img.qammunity.org/2020/formulas/mathematics/college/9ircz199gi5b7i4plvljyz5we0b69iyxah.png)
Dividing between 2 on both sides of the equation:
![x = \frac {1} {2}](https://img.qammunity.org/2020/formulas/mathematics/high-school/hj5w8zzsx7zaw6pppj50mzwg4ljbr1cuxp.png)
Answer:
![x = \frac {1} {2}](https://img.qammunity.org/2020/formulas/mathematics/high-school/hj5w8zzsx7zaw6pppj50mzwg4ljbr1cuxp.png)